Inter-species differences in biomarker responses and contaminat levels in three mysticete species (Balaenoptera musculus, Balaenoptera physalus and Balaenoptera edeni) of Gulf of California (Mexico). - FOSSI, MARIA CRISTINA; MARSILI, LETIZIA; Urban J.; Maltese S.; Coppola D.; Panti C.; Rojas Bracho L.; Jimenez B.; Munoz Arnaz J.; Finoia M. G. (2011)
The main objective of this project was to investigate the inter-species differences in CYP1A1 and CYP2B expression, gene biomarkers expression (AHR, E2F1 and ER1) and contaminant levels (OCs, PBDEs and PAHs) in three mysticete species, blue whale (Balaenoptera musculus), fin whale (Balaenoptera physalus) and Bryde’s whale (Balaenoptera edeni) of Gulf of California (Mexico) using skin biopsy as diagnostic tools. A suite of sensitive non-lethal biomarkers was applied to the three mysticete species in order to evaluate the toxicological status of this cetacean species in the Gulf of California and also to explore the role of migratory/resident “behavior” and the feeding habits (zooplankton-eating species fin whale and blue whale, fish-eating species Bryde’s whale) in the responses of the two isoforms of CYP. This “multi-trial diagnostic tool”, applied to skin biopsies, underlined differences in POP levels and molecular biomarker responses between the three mysticete species of Gulf of California. Two main factors seem to regulate the expression of different CYP isoforms in the three species studied: the inductive ability of POPs and PAHs and the different evolution of the two cytochromes related to the different feeding habits of the mysticete species. With regard to the level of contaminants the highest levels of PAHs and PCBs were detected in blue whale and the highest levels of DDTs and PBDEs were detected in fin whale in comparison to the fish-eating species (Bryde’s whale). Particular concern can be raised by the high levels of PCBs detected to in the migratory species blue whale, that could bioaccumulate POPs while moving along the Californian coast. This contamination phenomena can have generate induction of both CYP1A1 and CYP2B in this species and upregulation of estrogen receptor gene. On the opposite, extremely high level of both CYP1A1 and CYP2B were detected in the fish-eating species, showing similar level to odontocete species. Lower levels of OCs and high level of the CYP2B were detected in the ...